Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV METEOR during cruise M76/1b - Timothy G Ferdelman; Matthias Zabel (PANGAEA, 2025)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was continuously recorded during RV METEOR cruise M76/1b. Data was recorded on 18 days between 2008-04-26 and 2008-05-13. This dataset contains a survey data in the Namibian shelf area towards the continental slope (South Atlantic Ocean). The approximate average depth of the entire dataset is around 2700m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, data analysis of the multibeam raw data revealed that SVP has been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be seen already in the data due to the lack of proper SVP. Overall, it appears that the data quality is rather moderate since the gridded hillshade data showed some obstacles. Data can be processed e.g. with the open source software package MB-System (Caress et al. 2024, https://doi.org/10.5281/zenodo.6302801).